Hubungan Antara Indeks Massa Tubuh dan Riwayat Keluarga dengan Kejadian Anomali Refraksi pada Siswa Kelas 5 dan 6 SD Muhammadiyah Kleco - Muhammad Rafli Muzammil; Ahmad Ikliluddin (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Refractive anomalies in children are still an important vision problem to be treated. Refractive anomalies that are not handled properly at an age of children are prone to developing advanced vision problems such as lazy eye (amblyopia). Prevention needs to be carried out so that the occurrence of refractive anomalies in children can be minimized, one of which is by knowing the risk factors that trigger this refractive anomaly. This study aims to find a relationship between body mass index and family history of refractive anomalies and the incidence of refractive anomalies in children. The research was conducted on 5th and 6th grade students at SD Muhammadiyah Kleco, Yogyakarta. A total of 42 students with refractive errors were obtained, which was then analyzed regarding the relationship between body mass index and family history and the occurrence of refractive anomalies they experienced. A statistically significant relationship was obtained between family history and the incidence of refractive anomalies (p=0.009). There was no statistically significant relationship between body mass index and the incidence of refractive anomalies (p=0.321).